Professional-Oriented Competence of Future Teachers in the Context of Digital Adaptive Learning - Kurmasheva, Moldir; Zhorabekova, Ainur; Duisenova, Marzhan (Pedagogy and Psychology, 2025)
The study addresses the critical importance of teacher skills and competences in shaping educational quality and future generations, focusing on revealing the essence and structure of professionally based competences that prospective foreign language teachers should acquire to work effectively with digital adaptive technologies in their future profession. The research recognizes that improving teacher training programs and maintaining high teaching standards are essential for sustainable national development. Methodology and Methods. Data was collected using a structured Likert Scale questionnaire administered to 68 participants who rated a set of 25 competences. The research employed descriptive statistical analysis as the primary analytical approach, with the Friedman test utilized to reveal essential differences between professionally-based competences of prospective foreign language teachers. Results. The findings demonstrated that in-service teachers considered methodical competence as the most important professionally-based competence. The Friedman test revealed significant differences between various competences, with highest ranks assigned to competences related to effective lesson planning and classroom time management, while contemporary approaches such as hybrid learning models received the lowest rankings. The lower ranking of competences related to adaptive learning models indicated gaps in current teacher training programs. Scientific novelty. The research provides comprehensive analysis of the competence structure required for prospective foreign language teachers working with digital adaptive technologies, establishing a hierarchy of professional competences and identifying previously unrecognized gaps between traditional teaching skills and contemporary digital approaches in teacher preparation. Practical significance. The study reveals the need for focused professional development in teacher training programs, particularly in areas related to adaptive learning models and hybrid teaching approaches, providing evidence-based recommendations for improving the quality of foreign language teacher preparation to meet modern educational demands.